Waiting Times and Equilibrium Selection. - Beggs, A (Springer-Verlag, 2005)
This paper shows how graphs can be used to calculate waiting times in models of equilibrium selection. It also shows how reducing the state space can simplify the calculations of both waiting times and selected equilibria. The results are applied to potential games and games with strategic complementarities.